Correlation Between Waist-To-Hip Ratio (WHR) with Fasting Blood Glucose to The Risk of Type 2 Diabetes Mellitus in Tabaringan Health Center - Anas, Muhammad Werfhina Aswar; Kanang, Indah Lestari Daeng; Fattah, Nurfachanti; Nurmadilla, Nesyana; Hamzah, Pratiwi Nasir (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Diabetes mellitus is a serious long-term (or 'chronic') condition caused by increased levels of glucose in the blood because the body cannot produce one or enough of the insulin hormones, or cannot use the insulin it produces effectively. IDF data, the global prevalence of DM in 2019 is estimated at 9.3% (463 million people), increasing to 10.2% (578 million) in 2030 and 10.9% (700 million) in 2045 (IDF, 2019). Research results (Riskesdas) in 2018, the prevalence of diabetes mellitus in South Sulawesi diagnosed by doctors was 1.8% and 1.3%. WHR is a method for assessing fat accumulation in the body. The risk of DM is more related to intra-abdominal fat than subcutaneous fat. WHR was shown to be a better predictor of type 2 DM risk compared with BMI. The WHR limit for men in Asia Pacific is >0.9 and women >0.85. To determine the relationship between RLPP and fasting blood glucose levels in type 2 diabetes mellitus patients at the Tabarringan Community Health Center. This research is an analytical study using the Cross Sectional method, to determine the relationship between Fasting Blood Glucose and Waist-Hip Ratio. The research results showed that from 65 respondents a p-value was obtained of 0.514 > 0.05 so that Hnull was accepted and H1 was rejected. So the results obtained are that there is no relationship between WHR and fasting blood sugar levels. There is no relationship between WHR and fasting blood glucose levels in type 2 diabetes mellitus patients at the Tabarringan Community Health Center.